Peningkatan Kemampuan Literasi dan Numerasi Pembelajaran IPAS melalui Model Problem Based Learning Berbantuan Media Konkret Kelas V SDN Tambakrejo 01 Semarang - Ganang Aji Kurniawan, Ganang; Mira Azizah, Mira; Ida Dwijayanti, Ida; Erma Khristiyowati, Erma (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
Indonesia’s average score in reading literacy as reported by PISA in 2018 was 371, far below the average of 487. In fact, around 70% of Indonesian learners have not reached the basic level in understanding text. This indicates that the literacy and numeracy skills of Indonesian students are still low. The Problem Based Learning learning model is present to provide efforts to improve literacy and numeracy skills, so the purpose of this study is to improve the literacy and numeracy skills of grade V students of SDN Tambakrejo 01 Semarang in IPAS learning through the PBL model assisted by concrete media. This class action research was conducted in three cycles. The results showed an increasing trend in the initial average percentage of reading literacy 60.3% and numeracy literacy 55.4% to reading literacy 85.6% and numeracy literacy 80.3%. The conclusion is that the PBL model is proven effective in improving literacy and numeracy of fifth grade students of SDN Tambakrejo 01 Semarang with the help of concrete media in IPAS learning.